Special features of job satisfaction and efficiency of different professional type experts - FILATOVA, Olga (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The paper is devoted to the results of empirical research of specific features in job satisfaction and efficiency of the representatives of various professional groups: a „person – person”, a „person – equipment” and a „person – nature” professional types.